Efektivitas Intervensi Nonfarmakologis Terhadap Fungsi Kognitif Pada Pasien Demensia: A Systematic Review - Safaruddin; Hendra Dwi Kurniawan; Rizki Aqsyari (Jurnal Medicare, 2026)
Introduction: Dementia is a progressive neuro degenerative disorder characterized by a decline in cognitive function that affects memory, thinking, and daily activities. The increasing prevalence of dementia worldwide highlights the importance of effective management strategies, including non-pharmacological interventions. Objective: This study aimed to review the effectiveness of non-pharmacological interventions in improving cognitive function among patients with dementia. Methods: A systematic review was conducted using the PRISMA approach. Literature searches were performed in Pub-med, EMBASE, and Scopus databases for studies published between 2020 and 2026. Of the 2,904 articles identified, 10 studies met the inclusion criteria and were analyzed. Results: The review found that non-pharmacological interventions, particularly cognitive stimulation therapy and virtual reality-based interventions, were effective in maintaining and improving cognitive function. Additional benefits included enhanced quality of life and reduced loneliness. Music therapy, dance therapy, and lifestyle-based programs also demonstrated positive effects on cognitive outcomes. Conclusion: Non-pharmacological interventions are effective in supporting cognitive function and overall well-being in patients with dementia. These findings emphasize the importance of integrating multidisciplinary and multi-modal approaches into dementia care to promote independence, improve quality of life, and slow cognitive decline.